A holistic approach to CSR engagement in palm oil industry - Abdullah, Azwan; Mohd Radyi, Siti Amaliya; Yaacob, Mohd Rafi; Ismail, Mohammad; Zakaria, Mohd Nazri; Abdullah, Zulhamri (Institute of Advanced Science Extension (IASE), 2017)
This study presents a holistic framework in CSR activities by plantation companies that operate internationally. CSR activities are the most powerful element to support the sustainability of plantation operations in the international arena while respecting the available environmental resources. Using qualitative methods, this study has successfully developed a holistic framework that benefits all parties involved in CSR activities, especially in the plantation sector. The findings were based on information provided by respondents through interviews and field work observation method. Indeed, the cooperation of all parties, such as employers, employees, communities and the authorities seek to strengthen CSR activities more effectively and holistically.